Silica-coated nickel oxide a core-shell nanostructure: synthesis, characterization and its catalytic property in one-pot synthesis of malononitrile derivative. Issue 2 (3rd April 2017) - Chaudhary, Ratiram Gomaji; Tanna, J. A.; Mondal, A.; Gandhare, N. V.; Juneja, H. D.
ABSTRACT: We describe herein a unique approach to fabricate the silica-coated nickel oxide a core-shell nanostructure by using a different concentration of surfactant and characterized in terms of shape, size, and phase structure by means of various standard spectroscopic techniques like powder X-ray diffraction (PXRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and atomic force microscopy (AFM), while chemical composition identified by Fourier transform infrared (FTIR), UV–visible, and thermogravimetry/differential thermal analysis (TG/DTA). The effects of surfactant were authenticated in synthesis of nickel oxide nanoparticles. Furthermore, a simple and straightforward method was employed to synthesis of 2‐oxoindolin‐3‐ylidene malononitrile and their derivatives through Knoevenagel condensation in solvent-free condition using nanoparticle as a nanocatalyst. The derivatives were synthesized with an excellent yield and an eco-friendly. Remarkably, the catalyst was recovered by filtration from the model reaction, and it was used in the subsequent runs without further purification. However, an activity of the catalyst gets affected slightly for the next cycle in terms of yields. Abstract :